Quality Test of Drinks from Carica Papaya Tip with Addition of Artocarpus Heterophyllus L. - Diantiwi, Dinda; Nasution, Rizki Amelia (Newinera Publisher, 2024)
Drinks from papaya seeds and jackfruit have the potential to become functional drinks with health benefits. This study aims to test the quality of drinks from papaya seeds with the addition of jackfruit in various comparisons. The research method used was pre-test and post-test experimental design by analyzing data descriptively using table results. The quality parameters tested include antimicrobial tests on Escherchia colli bacteria, Staphyllococcus aureus bacteria, Candida albicans fungus using the disc diffusion method (well diffusion), vitamin C content test using the volumetric method, color, aroma, taste, and consumer liking with organoleptic testing. The results showed that the addition of jackfruit significantly had antibacterial effectiveness, and had vitamin C levels in composition 1 (5 gr papaya seeds) with a result of 0.2804%, and in composition 2 (4 gr papaya seeds: 1 gr jackfruit) with a result of 0.1400%. The color of the drink becomes brighter with the addition of jackfruit. The aroma and taste of the drink also became better with the addition of jackfruit. Based on the results of the consumer favorability test, drinks with a ratio of papaya seeds and jackfruit in composition 2 are most favored by panelists. Drinks from papaya seeds with the addition of jackfruit have good quality and are favored by consumers. This drink has the potential to become a functional drink with health benefits.